Medicinal plants sold at traditional markets in southern Ecuador - Tinitana Imaicela, F. (2016)
Background: The traditional markets in southern Ecuador and within the Andean region are especially important for plant resource trading among local people, even since before Spanish colonization; therefore, ethnobotanical studies are currently necessary and important. These strategic spaces persist for the traditional medicine cultural value reflected in the higher consumption of medicinal plants, which span all socioeconomic levels of rural and urban people. The purpose of this study includes the following: 1) to create a novel list of medicinal plants sold at 33 traditional markets; 2) to establish medicinal plant use agreement amongst vendors with the Factor of Informant Consensus (FIC); and 3) to determine the most sold medicinal plant species using the Fidelity Level (FL). Methods: This study focus on traditional markets ethnobotany utilizes the largest sample of medicinal plants market vendors up to date in Ecuador, interviewing them at 33 traditional markets, located within the Loja province. In order to determine the most sold medicinal plants and their ethnobotanical information, structured questionnaires and personal conversations were conducted with 196 medicinal plant vendors, and voucher specimens were created. Agreement among vendors about the therapeutic use of medicinal plants was measured using the FIC, and the most sold medicinal plant species were assessed with the FL. Results and discussion: This research registered 160 medicinal plant species, grouped in 126 genera and 57 families that were sold in 33 traditional markets. The uses of medicinal plants in southern Ecuador are related to a long history of traditional medicine health practices that has persisted until today as well as high plant diversity. The 53 therapeutic uses recorded were grouped into 12 medical categories that were adapted from the World Health Organization. Three medical categories shared the highest value for FIC = 0.92, which showed a high level of agreement of market vendors for 57 medicinal plant species sold to treat ailments related with digestive, dermatological, and sensorial systems. The FL index determined 11 culturally important medicinal plant species based on the reported uses by 40 or more market vendors. Two medicinal plant species had an FL = 100 %, Matricaria recutita and Gaiadendrum punctatum, used to treat digestive and respiratory systems ailments. Conclusions: In the Loja province, people continue to consume medicinal plant species sold at local markets to treat somatic and/or psychosomatic health ailments because sociocultural customs are strongly expressed in ancestral practices of wellbeing. When the largest values of FL (60.5 %-100 %) and FIC (0.81-0.92) indexes are combined, they demonstrated agreement among 196 market vendors in the use of seven medicinal plant species that were most sold for the 12 medical categories. This study stresses how important public policies are for the trade and quality of medicinal plant resources, particularly for local people practicing auto-medication. Reasons for the maintenance of traditional markets in southern Ecuador include lower cost of medicinal plants, confidence in traditional medicine, and/or sociocultural environment. In Ecuador, the sustainable management of wild medicinal plants diversity, particularly the most sold, is crucial for its conservation in nature. © 2016 The Author(s).